2000
DOI: 10.1053/euhj.1999.1869
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echocardiography-guided cardioversion of atrial fibrillation or flutter. Selection of a low-risk group for immediate cardioversion

Abstract: Aims Despite exclusion of left atrial thrombi by transoesophageal echocardiography, cardioversion-related thromboembolism has been reported in atrial fibrillation or flutter. To define a low-risk group for cardioversion without previous anticoagulation, patients were selected for immediate cardioversion if there were no thrombi, no echo spontaneous contrast and the outflow velocity of the left atrial appendage was greater than 0·25 m . s 1 on transoesophageal echocardiography. Methods and ResultsTwo hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 61 publications
2
22
0
3
Order By: Relevance
“…The treatment with warfarin sodium prior to electrical cardioversion was found to exceed the 4 weeks recommended in current guidelines, being approximately 12 weeks. Similar treatment duration with warfarin sodium was observed by Roijer et al [14]. Before start of treatment with warfarin sodium, the AF duration was <2 months for the majority (69%) of the patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The treatment with warfarin sodium prior to electrical cardioversion was found to exceed the 4 weeks recommended in current guidelines, being approximately 12 weeks. Similar treatment duration with warfarin sodium was observed by Roijer et al [14]. Before start of treatment with warfarin sodium, the AF duration was <2 months for the majority (69%) of the patients.…”
Section: Discussionsupporting
confidence: 81%
“…An important question is whether the results from the present study can be generalized. The data are in agreement with another Swedish study [14], but as similar studies from other countries are lacking, this question cannot be fully resolved. In addition, to improve the logistics of the precardioversion period in this patient group, it also seems important to evaluate whether the present recommended treatment duration can be decreased.…”
Section: Discussionsupporting
confidence: 66%
“…Roijer 34 and Fonseca 35 attempted to identify a low-risk group of patients for immediate cardioversion. To be eligible, patients had to be free of LA or LAA thrombus and SEC and have an LAA outflow velocity >0.25 m.s −1 .…”
Section: Reviews Continuedmentioning
confidence: 99%
“…In one nonrandomized trial using dalteparin, the rate of embolic events in cardioversion of atrial fibrillation was also low. 15 However, the effectiveness for the reduction of thromboembolic events in the arterial bed has not been shown consistently for all LMWHs. 22 In this study, phenprocoumon, commonly prescribed in Germany, was used as the oral anticoagulant instead of warfarin, which is the most widely used oral anticoagulant worldwide.…”
Section: Stellbrink Et Al Enoxaparin In Cardioversion Of Atrial Fibrimentioning
confidence: 99%
“…13 Moreover, the use of LMWH in patients with atrial fibrillation has been reported to be safe in patients with contraindications to oral anticoagulants 14 and effective in nonrandomized studies of atrial fibrillation cardioversion. 15 The aim of the present study was to compare the efficacy and safety of subcutaneous enoxaparin with conventional anticoagulation using intravenous UFH followed by the oral anticoagulant phenprocoumon in the setting of cardioversion of nonvalvular atrial fibrillation.…”
mentioning
confidence: 99%